(untitled) (Journal of Asian Development Studies, 2024)
A company’s performance is a complex phenomenon because of a variety of aspects to quantify it, however, a competitive criterion has been established by Pakistan Stock Exchange (PSX) in terms of "Top 25 Companies". Those firms qualifying this criterion over the last two decades need to be compared with those who have yet to achieve it. The main objective of the study is to evaluate the financial stability and extra-ordinary performance based on PSX quantitative criteria of those firms maintaining top 25 position over last 24 years. The financial aspects of 18 firms out of more than40 has been selected by taking last 24 years’ data. These firms are classified into two different samples, the sample from companies successfully qualify the criterion for "Top 25 Companies" award, while the second sample consist of other renowned ones that yet to qualify for this criterion. The performance evaluation of both types of firms has been done through financial statements available on the website of PSX through their annual reports to calculate the ratios. In addition to these financial ratios other relevant indicators considered for evaluation purposes are, equity premium as a difference in returns between stocks and less risky instruments (bonds), firm size measured through sales, and market performance measured through total assets. The impact of these ratios on the stock returns has also been evaluated through regression analyses which allowed to identify those specific advantages the ‘top-25 qualifier’ firms may have over the ‘other non- qualifier’ firms. The findings suggest that ‘top 25 qualifier’ firms mainly beat the ‘others non- qualifier’ based on equity-related measures including dividend payout ratios, market premium and the equity premium. Therefore ‘other non-qualifier’ should improve equity-related context to successfully qualify for this criterion in future.